‘It Never Ends’: Disability Advocacy and the Practice of Resilient Hope - Gould, James B. (Religions, 2024)
Political advocacy is an important religious practice. But social activism can be discouraging. This paper integrates moral theology, virtue ethics, positive psychology and spiritual formation to highlight the importance of resilient hope for social justice advocates. Part 1 describes an important justice issue—public services for disabled people. Part 2 defines transformational advocacy and outlines an advocacy theology. Part 3 analyzes despair and hope. Part 4 summarizes spiritual practices for building resilient hope.